2018
DOI: 10.1021/acs.jmedchem.7b01837
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Circulating Cancer Cells and Metastases in Breast-Cancer Models by a Potent EphA2-Agonistic Peptide–Drug Conjugate

Abstract: EphA2 overexpression has been associated with metastasis in multiple cancer types, including melanomas and ovarian, prostate, lung, and breast cancers. We have recently proposed the development of peptide-drug conjugates (PDCs) using agonistic EphA2-targeting agents, such as the YSA peptide or its optimized version, 123B9. Although our studies indicated that YSA- and 123B9-drug conjugates can selectively deliver cytotoxic drugs to cancer cells in vivo, the relatively low cellular agonistic activities (i.e., th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 63 publications
4
76
0
Order By: Relevance
“…While both agents seemed very active, ephrinA1-Fc caused a more sustained and extensive decrease in EphA2 levels even at day 3 after treatment, compared to prostate cancer cells treated with 135H12, where EphA2 levels returned after 2 days of treatment ( Figure 2 b). These observations have been made several times with similar agents and a variety of cell lines [ 14 , 15 , 17 , 18 , 21 ], including PC-3 [ 19 , 20 , 24 ], for example reported in Supplementary Figure S1 . While generally we observed that 135H12 has agonistic activity in the low-to sub-micromolar range [ 14 , 15 ], we tested it at 10 μM against PC-3 to assess the ability of the agent to cause a sustained internalization of the receptor over longer periods of time ( Figure 2 ), in view of its anticipated use in vivo.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…While both agents seemed very active, ephrinA1-Fc caused a more sustained and extensive decrease in EphA2 levels even at day 3 after treatment, compared to prostate cancer cells treated with 135H12, where EphA2 levels returned after 2 days of treatment ( Figure 2 b). These observations have been made several times with similar agents and a variety of cell lines [ 14 , 15 , 17 , 18 , 21 ], including PC-3 [ 19 , 20 , 24 ], for example reported in Supplementary Figure S1 . While generally we observed that 135H12 has agonistic activity in the low-to sub-micromolar range [ 14 , 15 ], we tested it at 10 μM against PC-3 to assess the ability of the agent to cause a sustained internalization of the receptor over longer periods of time ( Figure 2 ), in view of its anticipated use in vivo.…”
Section: Resultsmentioning
confidence: 89%
“…Recently, we reported that the dimeric version of 135H11 can efficiently suppress cell migration of pancreatic cancer cells [ 14 , 15 ]. In addition, we also reported previously that earlier generations of agonistic EphA2-targeting-peptide mimetics can be used as carriers for targeted delivery of chemotherapy to breast [ 17 ], pancreatic [ 15 , 18 ], and prostate cancer [ 19 , 20 , 21 ]. In the present study, we aimed at further evaluating the therapeutic potential of targeting EphA2 by agonistic agents 135H12 and ephrinA1-Fc to suppress tumor metastasis in an orthotopic nude-mouse model of prostate cancer.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Adapted with permission from [154]. Copyright (2017), American Chemical Society paclitaxel is found to be very useful in combating CTCs and preventing the lung metastasis in breast cancer models [168].…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
“…For example, a dimeric form of EphA2-targeting YSA peptide, when conjugated to paclitaxel, is effective in targeting circulating tumor cells and decreasing tumor size in prostate and pancreatic cancer xenograft models and in inhibiting metastases in breast cancer models (Barile et al, 2014; Salem et al, 2018b; Wu et al, 2015b) . Apart from targeting, these peptides can make the conjugated agents more soluble and bioavailable.…”
Section: Targeting the Eph/ephrin Complex For Drug Developmentmentioning
confidence: 99%